Strategies for Developing Holistic Learning Environments in Islamic Education: A Library Research Review - Difa Rahma Melati (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2026)
Modern education faces growing challenges, including academic pressure, digital media exposure, and moral decline, which demand a strategic rethinking of learning environments. In Islamic education, the goal is to develop insan kamil individuals who are intellectually capable, spiritually grounded, and morally upright. However, existing practices often prioritize cognitive achievement while neglecting spiritual and psychological dimensions. This study aims to analyze strategies for developing holistic learning environments that integrate spiritual and psychological aspects within Islamic educational settings. A qualitative library research method was employed, utilizing content analysis to systematically examine books, journal articles, and academic sources from relevant databases. The findings reveal that effective holistic learning environments are established through six interconnected strategies: integrative curriculum design linking religious and general knowledge, structured classroom management fostering emotional safety, spiritually enriched physical settings, value-based school culture grounded in akhlaq al-karimah, cultivation of emotional intelligence aligned with Islamic principles of self-purification, and active collaboration among schools, families, and communities. These findings imply that a balanced integration of spiritual values and psychological well-being is essential for holistic student development. Educational institutions should adopt this integrated framework to produce students who are academically competent, emotionally stable, and spiritually grounded.